The effect of protein supplement source or supply pattern on the intake, digestibility, rumen kinetics, nitrogen utilisation and growth of Ethiopian Menz sheep fed teff straw - Bonsi, M.L.K.; Tuah, A.K.; Osuji, P.O.; Nsahlai, V.I.; Umunna, N.N. (Elsevier, 1996)
A series of trials were conducted to study the effect of either nitrogen source or supply pattern on the growth, rumen fermentation pattern and utilisation of straw by Ethiopian Menz sheeAll experimental sheep were given teff straw basal diet (CON). Irrespective of the trial, treatment sheep were offered either cottonseed cake (CSC), leucaena (LEU) and sesbania (SESM) in the morning prior to teff straw. Additional treatments with sesbania were offered either in the evening (SESE) or morning and evening (SESME). Measurements included roughage intake, digestibility, kinetics, rumen fermentation patterns, nitrogen utilisation, microbial protein supply and growth of sheeRate of degradation was highest (P<0.05) when sesbania was offered once a day compared with twice a day, while supplementation produced higher (P<0.05) liquid passage rates. Diets with sesbania produced higher (P<0.05) roughage intake compared with leucaena. Microbial protein supply as well as N economy were similar (P<0.05) among the foliage diets irrespective of source, time or frequency of feeding. Supplementation enhanced (P<0.001) growth rates in sheep, while cottonseed cake (CSC) diet was superior (P<0.01) to the fodder trees. Growth rates declined across treatments during the second phase (6-10 weeks) compared with the initial period (1-6 weeks). It is also possible for farmers to feed sesbania supplements in the morning or evening or twice daily without any detrimental effects.